4h+-13=7h+3

Simple and best practice solution for 4h+-13=7h+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4h+-13=7h+3 equation:


Simplifying
4h + -13 = 7h + 3

Reorder the terms:
-13 + 4h = 7h + 3

Reorder the terms:
-13 + 4h = 3 + 7h

Solving
-13 + 4h = 3 + 7h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-7h' to each side of the equation.
-13 + 4h + -7h = 3 + 7h + -7h

Combine like terms: 4h + -7h = -3h
-13 + -3h = 3 + 7h + -7h

Combine like terms: 7h + -7h = 0
-13 + -3h = 3 + 0
-13 + -3h = 3

Add '13' to each side of the equation.
-13 + 13 + -3h = 3 + 13

Combine like terms: -13 + 13 = 0
0 + -3h = 3 + 13
-3h = 3 + 13

Combine like terms: 3 + 13 = 16
-3h = 16

Divide each side by '-3'.
h = -5.333333333

Simplifying
h = -5.333333333

See similar equations:

| x-14=-21 | | 4x-9=2x+15 | | x+25=2 | | y=-15-7x+4x^2 | | x(y+2)=y(6-7x) | | y=(4x+5)(x-3) | | -4x^2-5x-5=-5 | | x-4=-34 | | 12+3(z-4)=-2z+1 | | 10=3x-12.5 | | 1/2y+2=5 | | x-19=-14 | | 2x^2-28x=-2x^2-3x-36 | | 2(x-2)=-4+2x | | y=x^3-6x^2+9x-54 | | 4e^2x-3=20 | | x+9=52 | | 2x+5=6x-7x | | -x+5=2 | | F=5ab+9ab-ab | | 3(4x+5)=2(-10+5x) | | 6x^2-18x=-3x^2-2x-7 | | -.4=-.8u+.6u | | 5x^2+15x-15=5-6x | | 4x-22=14x-98 | | 1/2x^2-4/3x+4=0 | | 3x+7=-(4-3x) | | -4x^2-5x-5=0.75x-5 | | 3p+2=8+2p | | 25x-12=288 | | 12y=20y^2 | | 1/2b+6=11 |

Equations solver categories